Influence : how to raise your profile, manage your reputation and get noticed in a relationship economy - Cass, Warren, 1972- (Chichester, West Sussex, United Kingdom : John Wiley & Sons, 2017)
Stand out in a sea of "average" and start achieving your goals Success is not only a matter of what you know and who you know, it's also a matter of who knows you; by becoming a trusted contact and a source of answers, your influence expands - and so do your opportunities. This book will show you how to build influence from the ground up. You might already know that communication is key, but do you understand how different people communicate and how you should respond? Discover the power of networking and gain valuable advice for building the right relationships with the right people - and how to leverage those relationships where it counts. Influence is a powerful asset based on a simple concept, but the actual skills required to achieve it don't come naturally to most. However skills can be learned and this book provides expert instruction with real-world application to help you get to where you want to be. Master the art of communication and build rapport Raise your profile and manage your reputation Develop strategic relationships and grow your network Become the trusted go-to person in your field If you're ready to get more out of your job, your career and your life, Influence gives you the guidance and motivation you need to get moving.
Cover; Title Page; Copyright; Contents; Acknowledgements; Introduction; Why Read This Book?; So Why Me?; Making the Most of This Book; Chapter 1: What Is Influence?; Influence in a Changing World; The times, they are a changin'; Setting Objectives for Influence; Ask yourself; Specific; Measurable; Agreed upon; Realistic; Time-based; The Principles of Influence; Chapter 2: P Is for People -- Who do you know and, more importantly, who knows you?; Your Network; The Law of Reciprocity; Proactive connecting -- becoming the hub; Becoming a Connector; Know your network; Credibility by Association
Includes index.
CAS
Text in English
Keywords: Influence (Psychology); Reputation; Interpersonal relations